2009
DOI: 10.1016/j.cmet.2009.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Akt2 Is Required for Hepatic Lipid Accumulation in Models of Insulin Resistance

Abstract: Summary Insulin drives the global anabolic response to nutrient ingestion, regulating both carbohydrate and lipid metabolism. Previous studies have demonstrated that Akt2/protein kinase B is critical to insulin’s control of glucose metabolism, but its role in lipid metabolism has remained controversial. Here we show that Akt2 is required for hepatic lipid accumulation in obese, insulin-resistant states induced by either leptin-deficiency or high fat diet feeding. Lepob/ob mice lacking hepatic Akt2 failed to am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
246
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 248 publications
(279 citation statements)
references
References 61 publications
(71 reference statements)
25
246
7
Order By: Relevance
“…This finding is consistent with previous reports showing that heterozygous knockin mice carrying kinase-dead mutant p110a D933A do not exhibit abnormal glucose level and hyperglycemia is not worsened in the ob/ob mice lacking one Akt2 allele 26,30 . Indeed, we observed that the insulin-induced phosphorylation of Akt was further repressed by miR-378 overexpression, suggesting that the insulin resistance was worsened.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This finding is consistent with previous reports showing that heterozygous knockin mice carrying kinase-dead mutant p110a D933A do not exhibit abnormal glucose level and hyperglycemia is not worsened in the ob/ob mice lacking one Akt2 allele 26,30 . Indeed, we observed that the insulin-induced phosphorylation of Akt was further repressed by miR-378 overexpression, suggesting that the insulin resistance was worsened.…”
Section: Discussionsupporting
confidence: 83%
“…Given the fact that heterozygous knockin mice carrying kinasedead mutant p110a D933A do not exhibit abnormal glucose level, and hyperglycemia is not worsened in the ob/ob mice lacking one Akt2 allele 26,30 , we tested whether inhibition of hepatic p110a by miR-378 overexpression would reduce the hepatic lipid accumulation in ob/ob mice without exacerbating hyperglycemia. Interestingly, adenoviral-mediated delivery of miR-378/378* into the liver of ob/ob mice significantly reduced the liver weight and decreased the TG levels both in the liver and serum, but had no effect on fasting glucose level and body weight (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 Therefore, we hypothesized that retinoids might have a positive effect on liver steatosis affecting PTEN signaling, a complex PI3K/ AKT regulatory pathway involved in the control of hepatic glucose and lipid metabolism. 3,4 The role of PTEN in mediating the antisteatotic effect of ATRA is supported by our preliminary data. We studied the effect of ATRA in an in vitro model of hepatic steatosis using HepG2 cells supplemented with combined oleic acid (OA) and palmitic acid (PA) (molar ratio 2:1) at 1 mM final concentration.…”
supporting
confidence: 69%
“…1A). Inhibitor studies in cultured cells, and gene knockout experiments in mice, have shown that this pathway is required both for inhibition of FoxO1 activity (13,14) and for induction of SREBP-1c expression (15)(16)(17). Therefore, it is likely that the bifurcation must occur distal to Akt.…”
mentioning
confidence: 99%